Pendampingan Partisipatif Penyusunan Profil Perpustakaan Sebagai Upaya Penguatan Literasi Sekolah di SMA Negeri 1 Palembang - Ibrahim, Ibrahim; Arwan, Arwan; Kanada, Rabial; Puteri, Rafa Nabila; Sari, Novita Eka; Auliyah, Dwi Septi; Ramadhina, Tri Wahyuni (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
This Community Service activity aims to assist and enhance the school's capacity in developing a library profile as an effort to strengthen school literacy at SMA Negeri 1 Palembang. The method used in this Community Service program is participatory mentoring and training. The mentoring process is carried out in stages, starting from data collection, document preparation, to profile finalization. A well-structured library profile serves as a comprehensive overview of the library’s condition, facilities, services, and development programs. The field implementation involves socialization activities, training, and direct mentoring for the school library team. This activity is expected to help the school develop a standardized library profile, support library accreditation, and serve as a reference for the development of school literacy programs. The mentoring results indicate an improvement in the school’s understanding and ability to systematically and effectively compile a quality library profile. Additionally, it encourages students and educators to better understand the role of the library in supporting learning and strengthening literacy, assists the school in documenting library data—including book collections, facilities, services, and literacy programs—and fosters the development of a sustainable school literacy program. ABSTRAKKegiatan Pengabdian Kepada Masyarakat ini bertujuan untuk mendampingi dan meningkatkan kapasitas sekolah dalam menyusun profil perpustakaan sebagai upaya penguatan literasi sekolah di SMA Negeri 1 Palembang. Metode yang digunakan dalam Pengabdian Kepada Masyarakat yakni pendampingan dan pelatihan partisipatif. Pendampingan dilakukan secara bertahap mulai dari pengumpulan data, penyusunan dokumen, hingga finalisasi profil. Profil perpustakaan yang baik berfungsi sebagai gambaran lengkap mengenai kondisi, sarana, layanan, serta program pengembangan perpustakaan sekolah. Pelaksanaan di lapangan dilakukan melalui kegiatan sosialisasi, pelatihan, dan pendampingan langsung kepada tim perpustakaan sekolah. Kegiatan ini diharapkan dapat membantu sekolah memiliki profil perpustakaan yang sesuai standar, mendukung akreditasi perpustakaan, serta menjadi acuan dalam pengembangan program literasi sekolah. Hasil pendampingan menunjukkan peningkatan pemahaman dan kemampuan sekolah dalam menyusun profil perpustakaan secara sistematis dan berkualitas, mendorong peserta didik dan tenaga pendidik untuk lebih memahami peran perpustakaan dalam mendukung pembelajaran dan penguatan literasi, membantu pihak sekolah dalam mendokumentasikan data perpustakaan, termasuk koleksi buku, fasilitas, layanan, serta program literasi yang tersedia, juga mengembangkan program literasi sekolah yang berkelanjutan.